اعجاز القرآن پر ایچ ای سی کے منظور شدہ مجلات میں شائع شدہ مقالات کا جائزہ (Al-Qamar, 2023)
The topic of "Aʻjāz Qur'an" has also been discussed since the beginning. Although in the early centuries it was mentioned in the theological discourses of the theologians or in the commentaries of the commentators, very soon permanent compilations began to appear on the subject. Therefore, there is no century in which there is no increase in the scientific capital found on the subject of miracles of the Qur'an. The question arises as to how? How to convey the message of Islam to humanity with the help of Quranic sciences? The Holy Qur'an which was revealed to the last Prophet Muhammad ﷺ, just as he ﷺ is a collection of perfections, so the speech revealed to him ﷺ is also a collection of miracles. The Miracle of the Holy Qur'an the Qur'an is called Aʻjāz Qur'an in Islamic terms. The unique and unique ways of reciting the Holy Quran is one of its miracles. The Holy Quran challenged the opponents and deniers of the Holy Quran that if they are true, they should bring similar words or verses.
Keywords: Aʻjāz Qur'an; Dimensions; Terms; Synthesis; Islamic Sciences; Miracles; Quran; Miracles of the Quran; Thought and Science